A composite preparation method of a new energy battery diaphragm flame-retardant nano calcium carbonate

CN122898173APending Publication Date: 2026-10-13CHIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611096326.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]本发明的目的是提供一种新能源电池隔膜用阻燃纳米碳酸钙的复合制备方法,以解决现有技术中隔膜热稳定性不足、安全性差、界面结合弱等技术问题

Benefits of technology

[0022]1.本发明通过化学键合将磷氮阻燃剂锚定在纳米碳酸钙表面,克服了物理共混中阻燃剂易迁移、析出的问题,实现了阻燃高效性与持久性,通过硅烷偶联剂桥接、介孔二氧化硅包覆层以及热诱导交联,在无机填料、聚合物粘结剂和基膜之间构建了牢固的多层界面,防止涂层脱落。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898173A_ABST
    Figure CN122898173A_ABST
Patent Text Reader

Abstract

The application discloses a kind of new energy battery diaphragm with flame-retardant nano calcium carbonate composite preparation method, it is related to coating preparation technical field.The application includes the following steps: step 1. Preparation of flame-retardant functionalized nano calcium carbonate: nano calcium carbonate is treated with amino silane, obtain the nano calcium carbonate with amino on surface;Make it and phosphorus-containing flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide react under the action of catalyst, phosphorus nitrogen flame retardant layer is grafted on the surface of nano calcium carbonate by chemical bonding, obtain flame-retardant functionalized nano calcium carbonate, recorded as FR-CaCO3;Step 2. Form mesoporous silica shell layer: FR-CaCO3 obtained in step 1 is dispersed in alcohol solution containing pore-forming agent, add silicon source and catalyst, carry out hydrolysis condensation reaction, coat a layer of mesoporous silica shell layer on the surface of FR-CaCO3;Separate product after reaction, remove pore-forming agent by calcination, obtain core-shell structure material with mesoporous shell layer, recorded as mSiO2@FR-CaCO3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coating preparation technology, specifically a composite preparation method for flame-retardant nano-calcium carbonate for new energy battery separators. Background Technology

[0002] With the rapid development of new energy vehicles and energy storage technologies, the safety of secondary batteries such as lithium-ion batteries has become one of the key factors restricting their large-scale application. As a core component of the battery, the battery separator's thermal stability, mechanical strength, and electrolyte wettability directly affect the battery's safety performance and cycle life. Traditional polyolefin separators have low melting points and are prone to shrinkage and melting at high temperatures, leading to thermal runaway caused by contact between the positive and negative electrodes.

[0003] To improve the thermal stability of the diaphragm, existing technologies typically employ ceramic-coated diaphragms, which involve coating the base membrane surface with inorganic particles such as alumina and silica. However, these materials suffer from the following drawbacks: poor interfacial compatibility between inorganic particles and the polymer matrix, leading to easy detachment; particle agglomeration resulting in uneven coating; limited improvement in electrolyte wettability with simple physical coating; and the fact that most ceramic materials themselves lack flame-retardant properties, requiring the addition of additional flame retardants, which complicates the interfacial structure.

[0004] Nano-calcium carbonate (CaCO3) is considered a potential functional filler due to its wide availability, low cost, good thermal stability, and environmental friendliness. However, ordinary nano-calcium carbonate has high surface polarity, resulting in poor dispersibility in non-polar polymers and lacking flame-retardant properties. Although there are existing studies on surface-modified nano-calcium carbonate, these mainly focus on improving dispersibility, resulting in limited flame-retardant efficiency and insufficient bonding with the membrane matrix, making it prone to detachment from the matrix during long-term cycling.

[0005] Therefore, the present invention aims to develop a composite nano-calcium carbonate material that combines high flame retardancy, excellent interfacial compatibility, good electrolyte wettability and high ionic conductivity, and to apply it to battery separators.

[0006] The information disclosed above in this background section is only for enhancing the understanding of the background section of this invention, and therefore may include prior art that is not known to those skilled in the art. Summary of the Invention

[0007] The purpose of this invention is to provide a composite preparation method for flame-retardant nano-calcium carbonate for new energy battery separators, so as to solve the technical problems of insufficient thermal stability, poor safety and weak interfacial bonding in the prior art.

[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators, comprising the following steps:

[0009] Step 1. Preparation of flame-retardant functionalized nano-calcium carbonate: Nano-calcium carbonate is subjected to amino-silanization treatment to obtain nano-calcium carbonate with amino groups on the surface; then it is reacted with phosphorus-containing flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide under the action of a catalyst, and a phosphorus-nitrogen flame retardant layer is grafted onto the surface of nano-calcium carbonate through chemical bonding to obtain flame-retardant functionalized nano-calcium carbonate, denoted as FR-CaCO3;

[0010] Step 2. Formation of a mesoporous silica shell: The FR-CaCO3 obtained in Step 1 is dispersed in an alcohol solution containing a pore-forming agent, a silicon source and a catalyst are added, and a hydrolysis-condensation reaction is carried out to coat the surface of FR-CaCO3 with a mesoporous silica shell; after the reaction, the product is separated, and the pore-forming agent is removed by calcination to obtain a core-shell structured material with a mesoporous shell, denoted as mSiO2@FR-CaCO3;

[0011] Step 3. Interface Fusion and Composite Membrane Preparation: The mSiO2@FR-CaCO3 composite material obtained in Step 2 is dispersed with a fluorinated polymer binder and a crosslinking agent in an organic solvent to form a uniform slurry; the slurry is coated on the surface of a polyolefin porous base membrane, and then subjected to programmed temperature drying and heat treatment to allow the fluorinated polymer binder to crosslink and tightly bond with the silanol groups on the surface of mSiO2@FR-CaCO3 and the surface of the base membrane, thereby obtaining the flame-retardant nano-calcium carbonate composite membrane.

[0012] Preferably, in step 1, the average particle size of the nano-calcium carbonate is 30-80 nm; the silane coupling agent used in the aminosilanization treatment is γ-aminopropyltriethoxysilane, and its amount is 1%-5% of the mass of the nano-calcium carbonate; the amount of the phosphorus-containing flame retardant DOPO is 10%-30% of the mass of the nano-calcium carbonate; the reaction is carried out under nitrogen protection at 80-100°C for 4-6 hours.

[0013] Preferably, in step 2, the pore-forming agent is polyethylene glycol with a molecular weight of 400-2000; the silicon source is tetraethyl orthosilicate, and its amount is 5%-20% of the mass of FR-CaCO3; the catalyst is ammonia water; the calcination is carried out under an inert atmosphere at a temperature of 450-550℃ for 2-4 hours.

[0014] Preferably, in step 2, the thickness of the mesoporous silica shell is 5-20 nm and the pore size is 2-10 nm.

[0015] Preferably, in step 2, the fluoropolymer binder is polyvinylidene fluoride-hexafluoropropylene copolymer; the crosslinking agent is dicumyl peroxide, and its dosage is 0.5%-2% of the total solid content of the slurry.

[0016] Preferably, in step 3, the mass ratio of the mSiO2@FR-CaCO3 composite material to the fluoropolymer binder is 1:4 to 1:9.

[0017] Preferably, in step 3, the organic solvent is N-methylpyrrolidone; and the polyolefin porous base membrane is a polyethylene membrane, a polypropylene membrane, or a PE / PP composite membrane.

[0018] Preferably, in step 3, the programmed temperature rise drying and heat treatment includes three stages: the first stage is 80-100℃ to remove most of the solvent; the second stage is 120-140℃ to partially melt the fluoropolymer binder; and the third stage is 160-180℃ to initiate the crosslinking reaction.

[0019] The present invention also provides a flame-retardant nano-calcium carbonate composite material for new energy battery separators prepared by the method described above. The composite material has a core-shell structure with flame-retardant functionalized nano-calcium carbonate as the core and mesoporous silica as the shell, and a phosphorus-nitrogen flame-retardant layer is grafted onto the surface of the flame-retardant functionalized nano-calcium carbonate through chemical bonds.

[0020] The present invention also provides a new energy battery separator, comprising a polyolefin porous base membrane and a functional coating coated on at least one surface thereof, wherein the functional coating comprises the flame-retardant nano-calcium carbonate composite material as described above and a fluorinated polymer binder bonded thereto through a cross-linked network.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. This invention anchors phosphorus and nitrogen flame retardants onto the surface of nano-calcium carbonate through chemical bonding, overcoming the problems of easy migration and precipitation of flame retardants in physical blending, and achieving high efficiency and durability in flame retardancy. Through silane coupling agent bridging, mesoporous silica coating layer and thermally induced crosslinking, a strong multilayer interface is constructed between inorganic filler, polymer binder and base film to prevent coating peeling.

[0023] 2. This invention, through its mesoporous silica shell and the interpenetrating network structure formed with polymers, not only improves the adsorption and retention capacity of electrolyte, but also provides a low-impedance path for lithium-ion transport, which helps to improve the rate performance of the battery.

[0024] 3. This invention utilizes the combined action of a nano-calcium carbonate core, a flame-retardant layer, and a silica shell to effectively absorb heat, promote carbonization on the membrane surface to form a protective layer, and significantly improve the membrane's heat shrinkage resistance and high-temperature dimensional stability. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this invention. For those skilled in the art, other drawings can be obtained based on these drawings.

[0026] Figure 1 This is a flowchart of the preparation method of the present invention;

[0027] Figure 2 This is a schematic diagram of the core-shell structure composite material of the present invention;

[0028] Figure 3 This is a schematic diagram of the composite diaphragm structure of the present invention;

[0029] Figure 4 This is a schematic diagram of the interface bonding mechanism of the present invention. Detailed Implementation

[0030] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0031] This invention provides a method for preparing flame-retardant nano-calcium carbonate composites for new energy battery separators, comprising the following steps:

[0032] Step 1. Preparation of flame-retardant functionalized nano-calcium carbonate

[0033] Nano-calcium carbonate with an average particle size of 30-80 nm is dispersed in deionized water to form a suspension with a mass fraction of 5%-15%.

[0034] Add silane coupling agent γ-aminopropyltriethoxysilane (KH-550) at an amount of 1%-5% of the mass of nano-calcium carbonate, and stir at 60°C for 2 hours to obtain aminated nano-calcium carbonate.

[0035] The above product was dispersed in ethanol, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and a catalyst were added. The reaction was carried out under nitrogen protection at 80-100°C for 4-6 hours. The amount of DOPO used was 10%-30% of the mass of the nano-calcium carbonate. The reaction caused an addition reaction between the pH bonds of DOPO and the amino groups on the surface of the nano-calcium carbonate, forming a chemically bonded phosphorus-nitrogen synergistic flame-retardant layer.

[0036] After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain flame-retardant functionalized nano-calcium carbonate, denoted as FR-CaCO3.

[0037] Step 2. Forming a mesoporous silica shell

[0038] FR-CaCO3 was dispersed in an ethanol solution containing the pore-forming agent polyethylene glycol (PEG) and then ultrasonically dispersed until uniform.

[0039] Tetraethyl orthosilicate (TEOS) and ammonia were added, and the hydrolysis-condensation reaction was carried out at room temperature for 6-12 hours. The amount of TEOS used was 5%-20% of the mass of FR-CaCO3, with the aim of coating the surface of FR-CaCO3 with a mesoporous silica (mSiO2) shell.

[0040] After the reaction, the pore-forming agent was removed by centrifugation and calcination at 450-550℃ for 2-4 hours under an inert atmosphere, yielding a core-shell structured material with a mesoporous shell, denoted as mSiO2@FR-CaCO3. This mesoporous structure can adsorb electrolyte, improve wettability, and provide channels for ion transport.

[0041] The thickness of the mesoporous silica shell is 5-20 nm, and the pore size is 2-10 nm.

[0042] Step 3. Interface fusion and composite membrane preparation:

[0043] The above-mentioned mSiO2@FR-CaCO3 and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) copolymer were dispersed in N-methylpyrrolidone (NMP) at a mass ratio of 1:4 to 1:9 to form a homogeneous slurry. PVDF-HFP exhibits good electrochemical stability and adhesion. Dicumyl peroxide (DCP), a crosslinking agent accounting for 0.5%-2% of the total solids content, was added and pre-dispersed in the slurry.

[0044] The slurry is coated onto one or both sides of a polyolefin porous membrane using slot coating or doctor blade coating methods to form a wet membrane. The polyolefin porous membrane is a polyethylene (PE) membrane, a polypropylene (PP) membrane, or a PE / PP composite membrane.

[0045] The wet membrane was sequentially subjected to a three-stage temperature-drying process: the first stage was 80-100℃ to remove most of the solvent; the second stage was 120-140℃ to partially melt PVDF-HFP; and the third stage was a brief heat treatment at 160-180℃, slightly higher than the decomposition temperature of DCP, to initiate a cross-linking reaction, so that PVDF-HFP and the silanol groups on the surface of mSiO2@FR-CaCO3 and the surface of the base film formed a strong chemical and physical bond, ultimately yielding a composite membrane.

[0046] Example 1:

[0047] Step 1: Weigh 10g of nano-calcium carbonate with an average particle size of 50nm, disperse it in 100mL of deionized water, and sonicate for 30 minutes to form a suspension with a mass fraction of 10%. Add 0.3g of KH-550, and react mechanically at 60℃ under a nitrogen atmosphere for 2 hours. Centrifuge, wash, and dry to obtain aminated nano-calcium carbonate.

[0048] Step 2: The above product was dispersed in 150 mL of anhydrous ethanol, 2 g of DOPO and a small amount of triethylamine catalyst were added, and the mixture was refluxed at 90 °C for 5 hours under nitrogen protection. After the reaction was completed, the mixture was centrifuged, washed three times with ethanol, and dried under vacuum at 60 °C for 12 hours to obtain FR-CaCO3.

[0049] Step 3: Disperse 5g of FR-CaCO3 in 100mL of ethanol solution containing 0.5g of PEG-1000 and sonicate for 1 hour. Add 0.5g of TEOS and 2mL of ammonia solution sequentially with stirring, and react at room temperature for 8 hours. Collect the product by centrifugation, wash with ethanol, and calcine at 500℃ for 3 hours under a nitrogen atmosphere to obtain mSiO2@FR-CaCO3.

[0050] Step 4: Dissolve 1.5g mSiO2@FR-CaCO3 and 8.5g PVDF-HFP in 90g NMP and stir for 12 hours to form a homogeneous slurry. Add 0.05g DCP and continue stirring for 1 hour.

[0051] Step 5: Using a doctor blade coater, the slurry is evenly coated onto both sides of a 16 μm thick PE base film, with a wet film thickness of 10 μm on both sides. The coated separator is then subjected to drying and heat treatment in an oven at 90℃ for 5 min, 130℃ for 3 min, and 170℃ for 1 min in sequence. After cooling, it is wound up to obtain the composite separator.

[0052] Example 2:

[0053] Example 2 is basically the same as Example 1 in terms of steps, except that: in step 1, the amount of KH-550 is changed to 0.5g; in step 2, the amount of DOPO is changed to 3g; in step 3, the amount of TEOS is changed to 1g; and in step 4, the mass ratio of mSiO2@FR-CaCO3 to PVDF-HFP is changed to 2:8, that is, 1.5g and 6g.

[0054] Example 3:

[0055] Example 3 is basically the same as Example 1 in terms of steps, except that: in step 4, the polymer is replaced with a polyimide (PI) precursor solution with a solid content of 20%, and the DCP crosslinking agent is omitted; the drying and heat treatment procedure is changed to: 100°C, 10 min, pre-curing, and then stepwise heating to 300°C for 2 h for imidization.

[0056] Comparative Example 1:

[0057] Comparative Example 1 is basically the same as Example 1 in terms of steps, except that the DOPO grafting reaction in step 2 and the mesoporous silica coating in step 3 are not performed. Instead, the KH-550 modified nano-calcium carbonate is directly coated with PVDF-HFP composite onto the PE base film according to steps 4 and 5 of Example 1.

[0058] Comparative Example 2:

[0059] Comparative Example 2 uses commercially available ordinary nano-alumina with a particle size of about 50 nm, and is coated with PVDF-HFP composite onto a PE base film according to the formulation and process of steps 4 and 5 of Example 1.

[0060] The membranes prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests:

[0061] 1. Heat Shrinkage Rate: The diaphragm sample was cut into 10 cm × 10 cm squares, placed horizontally in an oven at 150℃ for 1 hour, and then cooled to room temperature before measuring the dimensional change. Heat shrinkage rate = (L0 - L1) / L0 × 100%, where L0 is the initial length and L1 is the length after heating. The test results are shown in Table 1 below:

[0062] Table 1. Results of Heat Shrinkage Performance Test

[0063]

[0064] As can be seen from the above, the thermal shrinkage rates of Examples 1-3 are all less than 2%, which is significantly lower than that of Comparative Examples 1 and 2. This indicates that by using the DOPO grafted flame retardant layer and the mesoporous SiO2 coating, a composite structure with higher thermal stability is formed, which effectively suppresses the movement of polymer chain segments at high temperatures and improves dimensional stability.

[0065] 2. Electrolyte Contact Angle: Using a contact angle meter, 1 μL of 1M LiPF6 in EC / DMC electrolyte was dropped onto the diaphragm surface. The droplet morphology was recorded and the static contact angle was calculated. Five points were tested for each sample, and the average value was taken. The test results are shown in Table 2 below:

[0066] Table 2. Electrolyte contact angle performance test results

[0067]

[0068] As can be seen from the above, the electrolyte contact angles of Examples 1-3 are all below 20°, while those of Comparative Example 1 are as high as 35°. This indicates that the mesoporous SiO2 shell has a high specific surface area and hydrophilicity, which significantly improves the electrolyte wetting ability and is beneficial to ion transport and battery interface compatibility.

[0069] 3. Ionic conductivity (25℃): Two stainless steel plates were used as blocking electrodes, with the diaphragm impregnated with electrolyte and sandwiched between them. Electrochemical impedance spectroscopy (EIS) was used to measure the conductivity in the frequency range of 0.1 Hz–1 MHz. The formula for calculating ionic conductivity is: Where d is the diaphragm thickness, R is the bulk impedance, and A is the effective contact area of ​​the electrode. The test results are shown in Table 3 below:

[0070] Table 3. Test results of ionic conductivity performance

[0071]

[0072] As can be seen from the above, the ionic conductivity of Examples 1-3 is all higher than 1.0 mS / cm, with Example 2 having the highest conductivity. This indicates that the mesoporous structure provides a continuous ion transport channel, and the flame retardant layer does not block the pores, thus synergistically improving the electrochemical performance.

[0073] 4. Flame retardancy: According to the UL-94 vertical burning standard, a 125 mm × 13 mm diaphragm sample was vertically fixed and ignited with a standard flame for 10 seconds. The self-extinguishing time, whether it dripped, and whether it ignited the absorbent cotton were recorded. The test results are shown in Table 4 below:

[0074] Table 4. Flame retardant performance test results

[0075]

[0076] As can be seen from the above, the flame retardancy of Examples 1-3 all reached UL-94 V-0 level, while Comparative Example 1 was only V-2 level and Comparative Example 2 was V-1 level. This shows that DOPO chemical grafting achieved phosphorus and nitrogen synergistic flame retardancy, and the mesoporous SiO2 further isolated heat and oxygen, thereby significantly improving the flame retardancy efficiency.

[0077] 5. Peel Strength: A 180° peel test was conducted. The membrane coating surface was fixed to the base membrane with adhesive tape on a tensile testing machine, and peeling was performed at a speed of 50 mm / min. The average peel force was recorded, and the peel strength per unit width (N / cm) was calculated. The test results are shown in Table 5 below:

[0078] Table 5. Peel strength test results

[0079]

[0080] As can be seen from the above, Example 3 exhibits the highest peel strength, indicating that the polyimide system forms a stronger interfacial bond with the silanol groups on the SiO2 surface. Examples 1-2 also show significantly higher peel strength than Comparative Examples 1-2, demonstrating that the fluoropolymer crosslinking system forms a robust physical-chemical bond network with the mesoporous SiO2 shell.

[0081] 6. Battery Cycle Performance: CR2032 coin cells were assembled using the prepared separator. The positive electrode was LiCoO2, and the negative electrode was lithium foil. The cells were cycled 100 times at a charge-discharge rate of 0.5 C, and the capacity retention was recorded. The test results are shown in Table 6 below:

[0082] Table 6. Battery Cycle Performance Test Results

[0083]

[0084] As shown above, the capacity retention rates of Examples 1-2 are all above 93%, indicating that the composite membrane has structural stability and low interfacial impedance during long-term cycling. In contrast, Comparative Example 1 exhibits faster capacity decay due to poor flame retardancy and weak interfacial bonding.

[0085] In summary, the composite nano-calcium carbonate material prepared by the method of this invention has the advantages of high flame retardancy, excellent interfacial compatibility, good electrolyte wettability and high ionic conductivity, and its application in battery separators has good market prospects.

[0086] The foregoing has only described certain exemplary embodiments of the present invention by way of illustration. Undoubtedly, those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the foregoing drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators, characterized in that: Includes the following steps: Step 1. Preparation of flame-retardant functionalized nano-calcium carbonate: Nano-calcium carbonate is subjected to amino-silanization treatment to obtain nano-calcium carbonate with amino groups on the surface; then it is reacted with phosphorus-containing flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide under the action of a catalyst, and a phosphorus-nitrogen flame retardant layer is grafted onto the surface of nano-calcium carbonate through chemical bonding to obtain flame-retardant functionalized nano-calcium carbonate, denoted as FR-CaCO3; Step 2. Formation of a mesoporous silica shell: The FR-CaCO3 obtained in Step 1 is dispersed in an alcohol solution containing a pore-forming agent, a silicon source and a catalyst are added, and a hydrolysis-condensation reaction is carried out to coat the surface of FR-CaCO3 with a mesoporous silica shell; after the reaction, the product is separated, and the pore-forming agent is removed by calcination to obtain a core-shell structured material with a mesoporous shell, denoted as mSiO2@FR-CaCO3; Step 3. Interface Fusion and Composite Membrane Preparation: The mSiO2@FR-CaCO3 composite material obtained in Step 2 is dispersed with a fluorinated polymer binder and a crosslinking agent in an organic solvent to form a uniform slurry; the slurry is coated on the surface of a polyolefin porous base membrane, and then subjected to programmed temperature drying and heat treatment to allow the fluorinated polymer binder to crosslink and tightly bond with the silanol groups on the surface of mSiO2@FR-CaCO3 and the base membrane surface, thereby obtaining the flame-retardant nano-calcium carbonate composite membrane.

2. The method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators according to claim 1, characterized in that: In step 1, the average particle size of the nano-calcium carbonate is 30-80 nm; the silane coupling agent used in the aminosilanization treatment is γ-aminopropyltriethoxysilane, and its amount is 1%-5% of the mass of the nano-calcium carbonate; the amount of the phosphorus-containing flame retardant DOPO is 10%-30% of the mass of the nano-calcium carbonate; the reaction is carried out under nitrogen protection at 80-100℃ for 4-6 hours.

3. The method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators according to claim 1, characterized in that: In step 2, the pore-forming agent is polyethylene glycol with a molecular weight of 400-2000; the silicon source is tetraethyl orthosilicate, and its dosage is 5%-20% of the mass of FR-CaCO3; the catalyst is ammonia water; the calcination is carried out under an inert atmosphere at a temperature of 450-550℃ for 2-4 hours.

4. The method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators according to claim 1, characterized in that: In step 2, the thickness of the mesoporous silica shell is 5-20 nm, and the pore size is 2-10 nm.

5. The method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators according to claim 1, characterized in that: In step 2, the fluoropolymer binder is polyvinylidene fluoride-hexafluoropropylene copolymer; the crosslinking agent is dicumyl peroxide, and its dosage is 0.5%-2% of the total solid content of the slurry.

6. A method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators according to claim 1 or 5, characterized in that: In step 3, the mass ratio of the mSiO2@FR-CaCO3 composite material to the fluoropolymer binder is 1:4 to 1:

9.

7. The method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators according to claim 1, characterized in that: In step 3, the organic solvent is N-methylpyrrolidone; the polyolefin porous base membrane is a polyethylene membrane, a polypropylene membrane, or a PE / PP composite membrane.

8. The method for preparing a composite of flame-retardant nano-calcium carbonate for new energy battery separators according to claim 1, characterized in that: In step 3, the programmed temperature rise drying and heat treatment includes three stages: the first stage is 80-100℃ to remove most of the solvent; the second stage is 120-140℃ to partially melt the fluoropolymer binder; and the third stage is 160-180℃ to initiate the crosslinking reaction.

9. A flame-retardant nano-calcium carbonate composite material for new energy battery separators prepared by the preparation method according to any one of claims 1-8, characterized in that, The composite material has a core-shell structure with flame-retardant functionalized nano-calcium carbonate as the core and mesoporous silica as the shell, and the surface of the flame-retardant functionalized nano-calcium carbonate is grafted with a phosphorus-nitrogen flame-retardant layer through chemical bonds.

10. A new energy battery separator, characterized in that, It includes a polyolefin porous base membrane and a functional coating coated on at least one surface thereon, the functional coating comprising the flame-retardant nano-calcium carbonate composite material of claim 9 and a fluoropolymer binder bonded thereto via a cross-linked network.